Determinants of Employee Engagement in Farley Sibu Sdn Bhd - Tay, Lee Chin (2012)
The purpose of this study is to examine and gain a better understanding of the drivers that influence the employee engagement in Farley Sibu Sdn. Bhd. 107 employees of Farley Sibu Sdn. Bhd. were participated in this study. Data were gathered through questionnaire analyzed by using Statistical Package for Social Science(SPSS) version 17. Throughout the statistical analysis-correlation analysis, it is found that there is a significant relationship between the three independent variables namely transformational leadership, career development and organization culture with the dependent variables-employee engagement. Among all three independent variable, transformational leadership is found to be the most important drivers in influencing the employee engagement in Farley Sibu Sdn. Bhd. Based on these findings, recommendations and suggestions were made to the management Farley Sibu Sdn. Bhd.